2004
DOI: 10.1055/s-2004-820935
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Turnover of Contractile Proteins in Volume-Overtrained Skeletal Muscle

Abstract: The purpose of this study was to find the composition shift of myosin heavy chain (MyHC) isoforms in overtraining in fast- and slow-twitch skeletal muscles and different changes in MyHC isofom composition, synthesis and turnover rate between 4-week and 6-week overtraining. Male Wistar rats were randomly assigned to 4-week and 6-week endurance training, 4-week and 6-week overtraining groups. Plantaris (Pla), extensor digitorum longus (EDL), and soleus (Sol) muscles were studied. Daily excretion of 3-methylhisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 20 publications
2
40
0
2
Order By: Relevance
“…Compared to the Co group, the Tr group exhibited a significant (P < 0.05) decrease in pure fiber IIA and IID CSA in the plantaris DR portion; there was also a tendency for pure fiber I and IIB CSA to decrease in this portion (P ¼ 0.08 and P ¼ 0.09, respectively). Our results are consistent with several studies which show a predominance of catabolic condition (Seene et al, 1999;Petibois et al, 2000;Seene et al, 2004) in situations with a persistent combination of excessive overload plus inadequate recovery (Jamurtas et al, 2000;Fatouros et al, 2006). Although the molecular events that underlie our findings remain unknown, these observations raise questions as to what signals and cellular conditions initiate muscle mass changes during overtraining conditions.…”
Section: Skeletal Muscle Changes During Resistance Trainingsupporting
confidence: 93%
See 4 more Smart Citations
“…Compared to the Co group, the Tr group exhibited a significant (P < 0.05) decrease in pure fiber IIA and IID CSA in the plantaris DR portion; there was also a tendency for pure fiber I and IIB CSA to decrease in this portion (P ¼ 0.08 and P ¼ 0.09, respectively). Our results are consistent with several studies which show a predominance of catabolic condition (Seene et al, 1999;Petibois et al, 2000;Seene et al, 2004) in situations with a persistent combination of excessive overload plus inadequate recovery (Jamurtas et al, 2000;Fatouros et al, 2006). Although the molecular events that underlie our findings remain unknown, these observations raise questions as to what signals and cellular conditions initiate muscle mass changes during overtraining conditions.…”
Section: Skeletal Muscle Changes During Resistance Trainingsupporting
confidence: 93%
“…These authors reported that overtraining syndrome in skeletal muscle may decrease capillarization impairing oxygen exchange between capillaries and muscle tissue which contributes to exercise intolerance. In this sense, considering that muscle fiber type is also classified according to the type of energy metabolism used (glycolytic or oxidative; Gunawan et al, 2007), our results together with those of Seene et al (2004), suggest that overtraining situations can result in a decrease in muscle oxidative capacity.…”
Section: Skeletal Muscle Changes During Resistance Trainingmentioning
confidence: 60%
See 3 more Smart Citations